Letter from Toronto: Post-World Pride 2014 Reflections on LGBTQ Art and Activism. (21st September 2014) - Phillips, Brian
Abstract : LGBTQ-themed exhibitions mounted by some of Toronto's key art institutions in conjunction with World Pride 2014 offered a significant opportunity to think about what (if anything specific) it is that we want or expect LGBTQ (lesbian, gay, bisexual, trans and queer) art to communicate directly about human community, human diversity and human dignity in the twenty-first century. In critiquing some of the work on display in these exhibitions, this practice note suggests a need for more LGBTQ-themed art that does full justice to formative individual experience but also moves outward from a preoccupation with self to remind spectators of worlds elsewhere. The work of South African photographer, Zanele Muholi, and of Moroccan novelist and film-maker, Abdellah Taïa, suggest fresh possibilities for a less parochial approach to exploring LGBTQ identities through various forms of cultural production.